A GIS Examination of the Chacoan Great North Road. Issue 1 (2nd January 2017) - Kunitz, J. K.; Lagree, J. D.; Weinig, D. L.
Abstract : This study uses geographic information systems (GIS) to examine the prehistoric road corridor that stretches north from Chaco Canyon to the San Juan River in northwestern New Mexico. Termed the "Great North Road, " this roadway has been extensively examined on the ground and with overhead photography and sensors. We apply GIS abilities to quantify descriptive measures of location, direction, and elevation and, in combination with previous work, compile the information to assess basic engineering choices made by the Chacoans in creating the road.